2021
DOI: 10.3389/fsurg.2021.715429
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tumors Misdiagnosed as Liver Hemangiomas

Abstract: Background and Aim: To derive lessons from the data of patients who were followed for various periods with the misdiagnosis of liver hemangioma and eventually found to have a malignancy.Material and Methods: The records of 23 patients treated between 2003 and 2018 were analyzed retrospectively.Results: Twelve patients were men and 11 were women; median (range) age was 55 (35–80). The principal diagnostic modality for the initial diagnosis was ultrasonography (n:8), magnetic resonance imaging (MRI) (n:13), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In another study, the ADC value in the differential diagnosis was found to be 2.30×10-3mm2/ and it was reported to have 55% sensitivity and 100% specificity [16]. In the study by Hardie et al, hepatic hemangiomas and metastatic lesions of the liver were compared and the mean ADC value of hemangiomas was found to be significantly higher than metastatic lesions [17]. Differential diagnosis for giant hemangiomas can always involve difficulties.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, the ADC value in the differential diagnosis was found to be 2.30×10-3mm2/ and it was reported to have 55% sensitivity and 100% specificity [16]. In the study by Hardie et al, hepatic hemangiomas and metastatic lesions of the liver were compared and the mean ADC value of hemangiomas was found to be significantly higher than metastatic lesions [17]. Differential diagnosis for giant hemangiomas can always involve difficulties.…”
Section: Discussionmentioning
confidence: 98%
“…Саркоматоїдна внутрiшньопечiнкова холангiокарцинома (сВХК) є надзвичайно рiдкiсним пiдтипом ВХК, що за класифiкацiєю Всесвiтньої органiзацiї охорони здоров'я визначений як рак бiлiарного тракту (РБТ), морфологiчно подiбний до веретеноклiтинної саркоми, фiбросаркоми або злоякiсної фiброзної гiстiоцитоми, i характеризується саркоматоїдними змiнами рiзного ступеня вираженостi у пухлинi епiтелiального походження [1]. Цей тип пухлини зустрiчається в 2-4,5 % осіб з ВХК [2] та є складним з точ-ки зору дiагностики через те, що не має специфiчних лабораторних i радiологiчних ознак та може iмiтувати iншi вогнищевi ураження печiнки, такi, наприклад, як абсцес печiнки [3] або гемангiома печiнки [4]. Основною опцiєю лiкування сВХК є хiрургiчне видалення.…”
Section: Practicing Physicianunclassified